Občutljivost informacijskega sistema finančni kontroling za kontekst poslovnega sistema - Delidžakova-Drenik, Eli (Uporabna informatika (Ljubljana), 1998)
The paper is about the context-sensitivity of a financial management control system in a large company that goes through the process of organizational restructuring in an environment in transition. We investigate the evolution ofthe system in order to clarify the impact of context changes and how the system has adapted to them. Also, we try to induce from our experience guidelines for development of adaptables DSS. This paper is a report from practice. Its objective is to contribute our experiences to the understanding of the inevitable interaction between sensitivity and adaptation of DSS.
Keywords: informacijski sistemi; kontrola; poslovni sistemi